QUALITY OF LIFE OF ADOLESCENTS FROM FAMILIES IN UDMURTIYA AT THE TIME OF CHEMOPROPHYLAXIS OF TUBERCULOSIS - O.V. Moiseeva ("Paediatrician" Publishers LLC, 2009)
The article presents the analysis of quality of life of adolescents from Udmurtiya, undergoing prophylaxis of tuberculosis. Author used PedsQL 4.0 questionnaire. 50 adolescents and equal quantity of parents took part in the study. It was shown that the prophylaxis of tuberculosis was performed in adolescents from families with low education level and with low earnings of parents. They have statistically significantly low level of quality of life compared to healty children.Key words: adolescents, tuberculosis, chemoprophylaxis, quality of life.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):12-13)